Evolution of breeding systems in acrocephaline warblers - Leisler, Bernd; Winkler, Hans; Wink, Michael (Behavioral ecology and sociobiology, 2002)
Comparative analyses constitute an important complement to studies of adaptive behavior. Previous studies of avian mating systems considered the role of paternal care and habitat type on the evolution of polygyny. We extended those studies and included in our analyses the role of habitat quality, as characterized by food supply. Species in the monophyletic lineage of acrocephaline warblers (Acrocephalus, Chloropeta, Hippolais) are widely distributed, inhabit a variety of different habitats, and show a variety of breeding systems. We present a phylogenetic analysis of parental care and mating system characteristics in relation to ecological traits in 17 species. On the basis of a molecular phylogeny, we reconstructed patterns of changes from social monogamy to polygyny, and in paternal brood care. Specifically, we analyze the coevolution of brood care participation of males and social system, and how it relates to habitat quality. Furthermore, we assessed the phylogenetic inertia of mating systems. We found support for the hypothesis that change to highly productive habitats was associated with a greater emancipation of males from brood care, and with polygyny and promiscuity. Poor habitats, on the other hand, were associated with monogamy and the occurrence of helpers. In contrast to some morphological characters, mating systems appear to be phylogenetically labile. /// Los análisis comparativos constituyen un complemento importante de los estudios del comportamiento adaptativo. Estudios previos sobre los sistemas de apareamiento de las aves consideraron el papel del cuidado parental y el tipo de hábitat en la evolución de la poliginia. Nosotros extendimos dichos estudios e incluimos en nuestros análisis el papel de la calidad del hábitat en términos de la abundancia de alimento. Las especies en el linaje monofilético que incluye los géneros Acrocephalus, Chloropeta, e Hippolais (Sylviidae) están ampliamente distribuidas, habitan una variedad de ambientes diferentes y poseen una variedad de sistemas reproductivos. Presentamos un análisis filogenético del cuidado parental y de algunas características del sistema de apareamiento en relación a caracteres ecológicos en 17 especies. Con base en una filogenia molecular, reconstruimos los patrones de cambio de monogamia social a poliginia y del cuidado paterno de la nidada. Específicamente, analizamos la coevolución de la participación de los machos en el cuidado de la nidada y el sistema social, y cómo se relaciona con la calidad del hábitat. También evaluamos la inercia filogenética de los sistemas de apareamiento. Encontramos evidencia que apoya la hipótesis de que el cambio a hábitats altamente productivos estuvo asociado con una mayor emancipación de los machos del cuidado de la nidada, y con la poliginia y la promiscuidad. Por otro lado, los hábitats pobres estuvieron asociados con la monogamia y la presencia de ayudantes. A diferencia de algunos caracteres morfológicos, los sistemas de apareamiento parecen ser filogenéticamente lábiles.